DESIGNING SOCIAL REALITY IN THE SPACE OF GLOBAL INFORMATION NETWORKS - Ягодзінський, С.Н. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
The aim of this article is to determine the principles of social programming and the design of global information networks. The author bases on that information networks carry out the procedure of divergence over the field of social reality of the information society. So they determine the points of social tension, social balance and instability. Scientific novelty of a given research consists of elaboration the principles of the deployment of the social information infrastructure. They include the principles of coherence and recursion of information networks. The practical value of this approach consists in establishing that the introduction of Grid systems destroys the conceptualization of the Internet as a diversified, equitable, universal space, which deprives social institutions of economic, political, cultural and other kinds of contradictions. Branching network infrastructure leads to the fact that at the beginning of the XXI century, this value is not information, but a network platform for its layout, structuring and broadcasting. Global information networks acquire the status of a dynamic social resource. It is substantiated that the sociocultural potential of network technologies is oriented toward eliminating ‘digital inequality’ and ‘information barrier’. They were products of the linear stage of the formation of information networks. These days they slow civilizational progress at the level of social management. It’s the main results of this research. Based on the socio-cultural potential of global information networks is implemented in the form of social design and programming, principles of functioning of the information network system are revealed. The idea of the possibility of manipulating the public consciousness using the methods of distributed parallel computations and Petri algorithms is substantiated. The basic principles of social design in the space of information networks are established. The main principles are the integration of the theoretical, pragmatic and social components of information networks; correlations of the recursion of information networks with communicative competence and the communicative competence of social actors. These principles are realized in the space of language games as a kind of virtual communication. It is substantiated that the socio-philosophical analysis of the influence of innovative technologies on the transformation of social space reveals anthropological, sociocultural, cognitive, pragmatic and axiological aspects and contradictions of the network society. The directions for further research will be aimed at revealing the features of the transformation of modern social and communicative practices. Acquiring the properties of a social institution, the potential information discourse of information networks determines the principles of harmonization of social and political, economic and legal, cultural and historical structures in the process of organizing and managing social processes. Therefore, social design can be presented in terms of postmodern theory. In our opinion, it may be productive to use the term "rhizome" to understand and describe the directions of social design of a global society